Courtroom decorum and the rules of conduct: accounts of homicide co-victims’ experiences during criminal justice proceedings - Reed, Mark D. (Criminal justice studies, 2024)
The right to be present for criminal justice proceedings is one of the key rights afforded crime victims and their families. A neglected but important area of investigation pertains to the adherence to rules of conduct in order to safeguard court decorum. This qualitative study explores what rules of conduct are commonly experienced by and, in some cases, enforced against homicide co-victims while attending such proceedings. The sample consists of 27 co-victims connected to 23 separate cases where the homicides occurred in a major metropolitan area in the southeastern United States. Drawing upon focus group data, NVivo 12 was employed to identify and illustrate themes associated with rules of conduct. About one-half of the co-victims reported facing dilemmas or restrictions when particular rules were not followed or upheld by themselves or the defendants’ families. Though infrequent, some co-victims were warned or removed from court for wearing inappropriate attire or failing to control one’s emotions. For some rules, co-victims felt that they were treated differently from the defendant and defendant’s family. The study concludes by discussing ways that courts can better balance the needs of homicide co-victims with the rights of the accused in maintaining etiquette in the courtroom.